The Normative Aspect in the Contemporary Understanding of Spirituality - Andrzej Jastrzębski (Wrocławski Przegląd Teologiczny)
In today’s world, the concept of spirituality – which is more and more complex – has attracted a great deal of interest. As first named and developed in the Roman Catholic context, it now has become universal and nearly all-embracing. Today, not all current conceptions of spirituality are grounded in, or linked to religion. The Western thought has been dealing with it for some time now and the Polish academic milieu is likely to follow suit. Thus helping people mature in their spirituality has become far more demanding than it used to be in the past when one could refer to a set of guidelines, prescriptions or commandments developed within traditional religions. In this paper, we try to describe various concepts of spirituality and analyze some universal theoretical and empirically-based proposals of assessing when someone’s spiritual growth is healthy and when it is not.